2017
DOI: 10.1021/jacs.7b03262
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Markovnikov Hydroarylation of Unactivated Olefins via Pyridyl Radical Intermediates

Abstract: The intermolecular alkylation of pyridine units with simple alkenes has been achieved via a photoredox radical mechanism. This process occurs with complete regiocontrol, where single-electron reduction of halogenated pyridines regiospecifically yields the corresponding radicals in a programmed fashion, and radical addition to alkene substrates occurs with exclusive anti-Markovnikov selectivity. This system is mild, tolerant of many functional groups, and effective for the preparation of a wide range of complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…We have found that pyridyl halide activation via single electron reduction using photoredox catalysts 9 can be accomplished, and that the intermolecular reactivity of the resulting radical species can be dictated by the reaction conditions. 10 , 11 More specifically, we found that pyridyl radicals display nucleophilic reactivity in aqueous DMSO, and they readily couple with electron-poor alkenes. We questioned whether this approach could be translated to heteroaryl amino acid synthesis through radical conjugate addition to dehydroalanine derivatives.…”
Section: Introductionmentioning
confidence: 86%
“…We have found that pyridyl halide activation via single electron reduction using photoredox catalysts 9 can be accomplished, and that the intermolecular reactivity of the resulting radical species can be dictated by the reaction conditions. 10 , 11 More specifically, we found that pyridyl radicals display nucleophilic reactivity in aqueous DMSO, and they readily couple with electron-poor alkenes. We questioned whether this approach could be translated to heteroaryl amino acid synthesis through radical conjugate addition to dehydroalanine derivatives.…”
Section: Introductionmentioning
confidence: 86%
“…The electrophilic sulfonyl radical 7 would subsequently undergo facile radical addition to alkene to generate the nucleophilic benzylic radical 9. At this stage, we envisioned that radical-radical coupling between the transient benzylic radical 9 and the persistent pyridyl radical anion 4 would forge β-sulfonyl pyridine 10 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Due to the acidity of the benzylic proton and the good leaving ability of sulfone, alkyl sulfone 10 would be expected to undergo E1 elimination with the assistant of base, furnishing the final branched alkenylpyridine product 11, as well as sulfinate 6 that could be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, radical-based chemistry provides an alternative platform to address this challenge. Particularly, the groups of MacMillan, Jui, and others [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] have successfully demonstrated that visible light photocatalyzed cross-couplings of pyridines to access to alkylated pyridines under mild conditions, by taking advantage of unique reactivity of open-shell pyridyl radical species (Fig. 1b).…”
mentioning
confidence: 99%
“…Jui described reactions between various haloazaarenes 87 and a variety of unactivated (neutral) olefins 92 (Scheme 17). [44] By using 1.0 mol% Ir[dF(CF 3 )ppy] 2 (dtbbpy)PF 6 as a photosensitizer, 1.3 equiv. of HEH 44 as the electron and hydrogen atom source, and more importantly, CF 3 CH 2 OH instead of H 2 O/DMSO as the solvent, a series of anti-Markovnikov hydroarylation products 93 were obtained in 39 to 89 % yields.…”
Section: Reactions Of Haloazaarenesmentioning
confidence: 99%